2015
DOI: 10.3168/jds.2014-8938
|View full text |Cite
|
Sign up to set email alerts
|

Propidium monoazide combined with real-time PCR for selective detection of viable Staphylococcus aureus in milk powder and meat products

Abstract: Staphylococcus aureus is a spherical, gram-positive, pathogenic bacterium commonly associated with bovine mastitis and clinical infections. It is also recognized as a pathogen that causes outbreaks of food poisoning. The objective of this study was to develop and evaluate a rapid and reliable technique that combines propidium monoazide (PMA) staining with real-time quantitative (q)PCR to detect and quantify viable cells of Staph. aureus in milk powder and meat products. The inclusivity and exclusivity of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 33 publications
2
30
0
1
Order By: Relevance
“…For the purpose of distinguishing living and dead cells, several studies have applied propidium monoazide (PMA) to measure the living fraction of cells in processed or pasteurized milk (5, 34, 35). However, because raw milk has not undergone thermal processing and therefore likely contains a preponderance of living cells, we did not use PMA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of distinguishing living and dead cells, several studies have applied propidium monoazide (PMA) to measure the living fraction of cells in processed or pasteurized milk (5, 34, 35). However, because raw milk has not undergone thermal processing and therefore likely contains a preponderance of living cells, we did not use PMA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been recognized as a pathogen that causes outbreaks of food poisoning (Zhang et al, 2015b). S. aureus can contaminate a variety of foods such as salad, cheese, milk, fish, and meat (Alarcon et al, 2006; Vazquez-Sanchez et al, 2014).…”
Section: Ema/pma In Differentiation Of Viable Cells Of Staphylococcusmentioning
confidence: 99%
“…This conventional method takes from 5 to 6 days and has low sensitivity and specificity (Alarcon et al, 2006). Hence, conventional method may underestimate the level of contamination (Zhang et al, 2015b). …”
Section: Ema/pma In Differentiation Of Viable Cells Of Staphylococcusmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested the application of the qPCR method combined with a propidium monoazide (PMA) sample pre-treatment, which allows the exclusion of the dead cells in PCR amplification (García-Cayuela et al, 2009;Gensberger et al, 2014;Nocker et al, 2009;Zhang et al, 2015). The qPCR enables a more rapid and specific detection of the targeted organisms and PMA treatment facilitates the exclusion of false positive results caused by DNA from dead cells (Gensberger et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%